Clinical characteristics and drug susceptibility profiles of Mycobacterium abscessus complex infection at a medical school in Thailand - Songkiat Sukmongkolchai; Suthidee Petsong; Nont Oudomying; Ajala Prommi; Sunchai Payungporn; Warat Usawakidwiree; Kanphai Wongjarit; Gompol Suwanpimolkul; Kiatichai Faksri; Chusana Suankratay; Suwatchareeporn Rotcheewaphan (BMC, 2023)
Abstract Objectives This study investigated the differences in epidemiological and clinical data, and antimicrobial susceptibilities among different subspecies of Mycobacterium abscessus complex (MABSC) clinical isolates at a medical school in Thailand. Methods A total of 143 MABSC clinical isolates recovered from 74 patients were genotypically analyzed for erm(41), rrl, and rrs mutations, and antimicrobial susceptibilities were determined using a broth microdilution method. Patient characteristics and clinical outcomes were reviewed from the medical records. Results Seventy-four patients were infected with 28/74 (37.8%) M. abscessus subspecies abscessus (MAB), 43/74 (58.1%) M. abscessus subsp. massiliense (MMA), and 3/74 (4.1%) M. abscessus subsp. bolletii (MBO). The clinical findings and outcomes were generally indistinguishable between the three subspecies. All three subspecies of MABSC clinical isolates exhibited high resistance rates to ciprofloxacin, doxycycline, moxifloxacin, TMP/SMX, and tobramycin. MAB had the highest resistance rates to clarithromycin (27.8%, 20/72) and amikacin (6.9%, 5/72) compared to MBO and MMA, with p < 0.001 and p = 0.004, respectively. In addition, the rough morphotype was significantly associated with resistance to amikacin (8.9%, 5/56), clarithromycin (26.8%, 15/56), and imipenem (76.8%, 43/56) (p < 0.001), whereas the smooth morphotype was resistant to linezolid (57.1%, 48/84) (p = 0.002). In addition, T28 of erm(41), rrl (A2058C/G and A2059C/G), and rrs (A1408G) mutations were detected in 87.4% (125/143), 16.1% (23/143), and 9.1% (13/143) of MABSC isolates, respectively. Conclusions Three MABSC subspecies caused a variety of infections in patients with different underlying comorbidities. The drug susceptibility patterns of the recent circulating MABSC strains in Thailand were different among the three MABSC subspecies and two morphotypes.